Risk Assessment of Aging G+3 Residential Buildings - Resma B. Vijay; Vedant Kakade; Raj Madhav; Parth Shingote; Gauri Thorat (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The structural deterioration of ageing buildings in India presents significant safety hazards, necessitating systematic assessment and intervention measures. This study examines the efficacy of structural audits in evaluating and enhancing the stability of older buildings. The audit methodology encompasses comprehensive visual inspections and advanced non-destructive testing (NDT) techniques, including Rebound hammer tests, Ultrasonic pulse velocity tests, Carbonation tests, and Half-cell potential tests, to assess structural integrity. The overall health of Buildings based on visual inspection concludes that in the context of Mumbai’s Building and Construction Authority (BMC) classification of dilapidated buildings, Raj Laxman A1-B1 & A2-B2 Society falls under the C2B category (requires structural repairs but does not necessitate immediate evacuation of residents) On performing Rebound Hammer Test, it is found that Building A1-B1,17% of total Structural Elements Tested are comes under the fair condition while 83% of them are falls under poor Category and Building A2-B2,8% of total Structural Elements Tested are comes under the fair condition while 92% of them are falls under poor Category of Condition. On performing the UPV Test, it was found that all the tested elements fall under the medium category. Conducted Carbonation test results show that both Buildings A1-B1 and A2-B2 have no carbonation or a negligible depth of carbonation in the concrete. The probability of corrosion in the reinforcement of both Buildings A1-B1 and A2-B2 was approximately 70% as corrosion activity fell between 200mV & 350mV. Audit and Stability reports of both Buildings A1-B1 and A2-B2 prepared on the Visual inspections and NDT findings. Following the repair of the building, on performing Rebound Hammer Test it is found that Building A1-B1,50% of total Structural Elements Tested are comes under the good condition while 50% of them are falls under fair Category and Building A2-B2,60% of total Structural Elements Tested are comes under the good condition while 40% of them are falls under fair Category of Condition. The condition of the building was enhanced after taking up repair work, as suggested.